Pregnancy-induced complications in IgA nephropathy: A case report. Issue 15 (April 2018) - Chen, Hui; Li, Xuelan; Wu, Yue; Fan, Lihong; Tian, Gang
Abstract: Rationale: IgA nephropathy is one of the most common causes of renal hypertension. The clinical management of IgA renal patients during pregnancy is challenging, as complex pathophysiological changes may occur that affect both the patient's prognosis and the outcome of the pregnancy. Patient concerns: A 36-year-old woman with a family history of hypertension and at least one year of untreated mild high blood pressure was admitted to our hospital in the 28th week of pregnancy. She suffered from hypertensive disorder complicating pregnancy (HDCP) with renal insufficiency and stillbirth. Treatment with duplex antihypertensive drugs did not improve her blood pressure and she presented with abnormal renal function. Diagnoses: A renal biopsy led to the diagnosis of a grade IV IgA nephropathy (Lee's grading system) with renal hypertension. Interventions: The prescribed treatment regimen consisted of low dose cyclophosphamide 0.2 g per day for two days, followed by daily oral administration of 30 mg prednisone, 30 mg Nifedipine extended-release tablets and 80 mg Telmisartan to regulate the blood pressure. Outcomes: The medication with a combination of antihypertensive and immunosuppressive drugs led to a clinical improvement with a nearly normal renal function and a stable blood pressure during the one-year follow-up. Lessons: This case underlines that 1) the pregnancy outcomes of patients with IgA nephropathy are variable and depend on the renal function, blood pressure, status of urine proteins and the renal histological grade, and 2) especially female patients of childbearing age with hypertension need to be carefully examined to determine the cause of hypertension to avoid damage to target organs and complications during pregnancy.